Asuhan Keperawatan Jiwa Pada Ny.S Dengan Gangguan Persepsi Sensori Halusinasi Pendengaran di Ruang Srikandi Rumah Sakit Jiwa Daerah Surakarta - Anggara, Rizxy, Wachidah Yuniartika, S.Kep., Ns., M.Kep (2015)
Background: The high incidence of hallucinations in Surakarta Regional Mental Hospital during the month of February 2014 until February 2015 into a sequence number one with the number of 4,021 patients attract writers to do the soul of nursing care in patients with disorders of sensory perception: Hallucinations. Objective: Writer want to know, understand and can apply the nursing care to clients with impaired sensory perception: Hallucinations includes assessment, diagnosis, intervention, implementation and evaluation of nursing. Results: Writer wish after nursing care for 3x24 hours, patients can recognize hallucinations she experienced, can control the hallucinations with 4 ways, rebuke, conversing with others, doing the activity schedule, and drug therapy can run properly. Conclusion: Cooperation between the health team and the client or the client's family is indispensable for the success of the client's nursing care, therapeutic communication can encourage more cooperative clients, family is very important role in caring for clients with impaired sensory perception: Hallucinations. Keywords: sensory perception, auditory hallucinations